The Encyclopedia of Child and Adolescent Development 2020
DOI: 10.1002/9781119171492.wecad175
|View full text |Cite
|
Sign up to set email alerts
|

Positive Well‐Being

Abstract: There is almost universal consensus regarding the high importance and desirability of positive well‐being in children. Despite this consensus, the study of children has traditionally focused on their ill‐being (e.g., anxiety, depression, and loneliness) and not on their well‐being (e.g., happiness, life satisfaction, and thriving). This entry reviews measures of the components of children's well‐being using quantitative, qualitative, and mixed methods and discusses studies that use these methods to identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Other researchers have studied the relationship between goal profiles and life satisfaction. However, the literature does not provide a universally agreed-upon definition of life satisfaction, and the term is often used interchangeably with well-being, quality of life, and happiness (Holder and Graydon 2020;Statham and Chase 2010). Multiple studies have suggested that young adults' life satisfaction associates with the type of goals and outcomes they seek to attain.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Other researchers have studied the relationship between goal profiles and life satisfaction. However, the literature does not provide a universally agreed-upon definition of life satisfaction, and the term is often used interchangeably with well-being, quality of life, and happiness (Holder and Graydon 2020;Statham and Chase 2010). Multiple studies have suggested that young adults' life satisfaction associates with the type of goals and outcomes they seek to attain.…”
Section: Theoretical Frameworkmentioning
confidence: 99%